2021
DOI: 10.3171/2021.5.focus21206
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional–printed marker–based augmented reality neuronavigation: a new neuronavigation technique

Abstract: OBJECTIVE The aim of this study was to assess the precision and feasibility of 3D-printed marker–based augmented reality (AR) neurosurgical navigation and its use intraoperatively compared with optical tracking neuronavigation systems (OTNSs). METHODS Three-dimensional–printed markers for CT and MRI and intraoperative use were applied with mobile devices using an AR light detection and ranging (LIDAR) camera. The 3D segmentations of intracranial tumors were created with CT and MR images, and preoperative reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported on multiple evaluation metrics ( Supplemental Digital Content 3, Table 2 , http://links.lww.com/ONS/B49). 10-83,85-90 Based on the results of this review, the following evaluation categories have been defined: (1) registration accuracy, (2) clinical outcome, (3) time measurements, (4) task performance, (5) technical reliability, and (6) user perception (Table).…”
Section: Resultsmentioning
confidence: 99%
“…Augmented Reality that necessitates the use of markers (Marker Based Tracking) This method necessitates the use of a marker image, which is typically a black-andwhite square illustration with bold black borders and white background. The computer will then recognize the position and orientation of the marker object and generate a 3D display with the coordinates (0, 0, 0) and an axis made up of X, Y, and Z [7]. The camera is pointed at the marker image and recognizes the marker image and then displays a 3D object based on the recognized marker image.…”
Section: Augmented Realitymentioning
confidence: 99%
“…Here, we build on a more nascent approach to register and track anatomy and tools; one that leverages light detection and ranging (LiDAR) technology, a tracking technique that uses principles of radar, but with laser light instead of electromagnetic radiation. Existing literature has only studied the use of LiDAR in registration [ 41 ], not tracking of anatomy and tools. Further, no systematic comparison between visual and LiDAR‐based tracking accuracy has been performed.…”
Section: Introductionmentioning
confidence: 99%